A ubiquitin‐binding CUE domain in presenilin‐1 enables interaction with K63‐linked polyubiquitin chains. Issue 9 (18th March 2015) - Duggan, Stephen P.; Yan, Run; McCarthy, Justin V.
Abstract : The presenilins (PS1 and PS2) are the catalytic component of the γ‐secretase intramembrane protease complex, involved in the regulated intramembrane proteolysis of numerous type I transmembrane proteins, including amyloid precursor protein (APP) and Notch. Herein, we describe the identification and characterization of a CUE (coupling of ubiquitin conjugation to endoplasmic reticulum degradation) ubiquitin‐binding domain (UBD) in PS1, and demonstrate that the CUE domain of PS1 mediates non‐covalent binding to Lysine 63‐linked polyubiquitin chains. Our results highlight a γ‐secretase‐independent function for non‐covalent ubiquitin signaling in the regulation of PS1, and add new insights into the structure and function of the presenilin proteins. Abstract : Presenilins contain a CUE ubiquitin‐binding domain. PS1 CUE domain mediates non‐covalent binding to Lysine63‐linked polyubiquitin chains. PS1 CUE domain is dispensable for presenilin endoproteolysis and presenilin‐dependent γ‐secretase activity.